2017
DOI: 10.1038/srep46753
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Evaluate Ribosomal Performance in Cell-Free Protein Synthesis Systems

Abstract: Cell-free protein synthesis (CFPS) systems were designed to produce proteins with a minimal set of purified components, thus offering the possibility to follow translation as well as protein folding. In order to characterize the performance of the ribosomes in such a system, it is crucial to separately quantify the two main components of productivity, namely the fraction of active ribosomes and the number of synthesizing cycles. Here, we provide a direct and highly reliable measure of ribosomal activity in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…This includes coarse-grained ordinary differential equation (ODE) models containing effective lumped parameters and a small number of reactions (Mavelli et al, 2015;Carrara et al, 2018;Doerr et al, 2019), as well as more complex models based on modeling of a large number of elementary reactions, which can provide more detailed mechanistic insights but whose connection to experimental data as well as parameter inference is challenging (Matsuura et al, 2017(Matsuura et al, , 2018. These models show that a number of steps involving ribosomes could potentially become rate-limiting: these include slow elongation rates, peptide release, and ribosome dissociation; qualitatively similar results were observed experimentally (Kempf et al, 2017;Li et al, 2017;Doerr et al, 2019).…”
Section: Recombinant Systemssupporting
confidence: 52%
“…This includes coarse-grained ordinary differential equation (ODE) models containing effective lumped parameters and a small number of reactions (Mavelli et al, 2015;Carrara et al, 2018;Doerr et al, 2019), as well as more complex models based on modeling of a large number of elementary reactions, which can provide more detailed mechanistic insights but whose connection to experimental data as well as parameter inference is challenging (Matsuura et al, 2017(Matsuura et al, , 2018. These models show that a number of steps involving ribosomes could potentially become rate-limiting: these include slow elongation rates, peptide release, and ribosome dissociation; qualitatively similar results were observed experimentally (Kempf et al, 2017;Li et al, 2017;Doerr et al, 2019).…”
Section: Recombinant Systemssupporting
confidence: 52%
“…Notably, recent reports propose a similar scenario for in vitro translation systems from E. coli , wherein it was demonstrated that ribosomes were only partially actively participating in translation ( Failmezger et al, 2017b ; Kempf et al, 2017 ). Hence, it might be suggested that limited ribosome activity represents a general bottleneck in CFPS.…”
Section: Resultsmentioning
confidence: 86%
“…Also, in order to tether the nascent chain in the optical tweezers a biotin tag was similarly introduced using another amber stop codon at the N-terminus of the nascent chain, which was synthesized by ribosomes biotinylated at the uL4 ribosomal protein (24). After synthesis, ADR1a remained attached to the ribosome due to translational arrest at the C-terminal SecMstr arrest peptide (AP), a strong AP designed based on an extensive mutagenesis screen (25,26) (Fig. 1B and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The amber stop codon TAG was added upstream the gene of ADR1a, followed by a sequence encoding for 6 histidines (6×His) and the ProX tag peptide that contains the fourbase codon CGGG for incorporation of unnatural amino acids (38). Similarly, another amber stop codon TAG was engineered downstream of the ADR1a gene, followed by a Gly / Ser rich linker and an enhanced variant of the SecM arrest peptide (SecMstr) (FSTPVWIWWWPRIRGPP) (26). The C-terminal extension was either engineered to be 26 or 34 residues long to allow folding of the protein domain inside or outside the ribosomal tunnel, respectively.…”
Section: Plasmid Constructionmentioning
confidence: 99%